2021
DOI: 10.1371/journal.pntd.0009988
|View full text |Cite
|
Sign up to set email alerts
|

Culex quinquefasciatus larvae development arrested when fed on Neochloris aquatica

Abstract: Culex quinquefasciatus is a cosmopolitan species widely distributed in the tropical and subtropical areas of the world. Due to its long history of close association with humans, the transmission of arboviruses and parasites have an important role in veterinary and public health. Adult females feed mainly on birds although they can also feed on humans and other mammals. On the other hand, larvae are able to feed on a great diversity of microorganisms, including microalgae, present in natural or artificial breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Additionally, many reports have shown that Cx. quinquefasciatus transmits sylvatic arbovirus from birds, indicating that it may function as an important bridge between sylvatic arbovirus transmission from birds to humans in urban areas ( Lopes et al., 2019 ; Gil et al., 2021 ; Pereira et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many reports have shown that Cx. quinquefasciatus transmits sylvatic arbovirus from birds, indicating that it may function as an important bridge between sylvatic arbovirus transmission from birds to humans in urban areas ( Lopes et al., 2019 ; Gil et al., 2021 ; Pereira et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We interpret this through a higher supply of nutrients, in particular N and P. However, this statement must be taken with caution as other nutrients were manipulated conjointly with N and P, and colimitation amongst different nutrients is common (Kaspari & Powers, 2016). The lack of difference in survival is more puzzling, especially when considering that C. quinquefasciatus is a generalist species whose larvae fare especially well in water with high organic loads (Gil et al, 2021;Roberts & Kokkinn, 2010;Santana-Martínez et al, 2017), which is the case of mesocosms that received leaf litter and faeces. It is possible that any increase in survival in those mesocosms that received leaf litter and faeces was counterbalanced by the production of noxious metabolites of microorganisms growing on remains of Rubus armeniacus (Rosales: Rosaceae), the food plant of C. morosus, the insects that produced the faeces.…”
Section: F I G U R Ementioning
confidence: 92%
“…All larvae were of a similar size, being from the same generation of a laboratory colony, and were randomly seeded within the mesocosms shortly after hatching to the first instar. This mosquito is a generalist species feeding on a broad variety of microorganisms and particulate organic matter through the filtering of water in its mouthparts (Gil et al, 2021;Merritt et al, 1992;Östman et al, 2008). This species can compete with other macroscopic filter-feeders such as cladocerans (Blaustein & Chase, 2007;Duquesne et al, 2011), so we ensured that no such organism was present within the mesocosms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since algae live in mosquito breeding areas, they are consumed as food by mosquitoes. Therefore, female mosquito species, such as Culex quinquefasciatus , choose areas containing microalgae as oviposition substrates ( Gil et al, 2021 ). In addition, algae make important contributions to mosquito control by supporting mosquito predators such as dragonflies and aquatic insects in the habitat they create ( Chaves & Koenraadt, 2010 ).…”
Section: Introductionmentioning
confidence: 99%